Influence of Periodontitis, Implant, and Prosthesis Characteristics on the Peri-Implant Status: A Cross-Sectional Study - Ioanna Papalou; Panagiota Vagia; Ahmet Cakir; Henri Tenenbaum; Olivier Huck; Jean-Luc Davideau (International Journal of Dentistry)
Background. The association between peri-implant diseases and the periodontal, implant, and prosthesis characteristics has been characterized in various ways. Purpose. The aim of this study was to evaluate the link between the peri-implant and periodontal status and the influence of implant and prosthesis parameters during implant follow-up. Materials and Methods. One hundred and seven patients with a total of 310 implants that had at least one year of function who were attending periodontal and implant maintenance at a university clinic setting were included in this cross-sectional study. The demographic, periodontal, peri-implant tissue, implant, and prosthesis parameters were recorded. A pocket depth > 4 mm with bleeding on probing defined periodontal/peri-implant soft tissue diseased sites. Analyses were performed at the patient and implant levels using univariable and multivariable mixed regression analysis. Results. The mean implant follow-up was 7.22 years. At the patient level, the bleeding on probing and pocket depth measurements were more pronounced around the implant than around the teeth. The opposite was observed for plaque and the clinical attachment levels. At the implant level, multivariable analysis showed that the periodontal and corresponding peri-implant tissue parameters, such as diseased sites, were closely related. The implant location, bone level, and number were selectively associated with the implant bone level, while cemented retention and emergence restoration profile influenced the implant pocket depth. Conclusions. The present study suggested that clinical peri-implant and periodontal soft tissue statuses were different, which could be a consequence of the initial implant and prosthesis healing process. However, during implant follow-up, the peri-implant parameters were predominantly associated with their corresponding periodontal parameters regardless of an association with the implant and prosthesis characteristics. This trial is registered with ClinicalTrials.gov ID: NCT03841656.